2014
DOI: 10.1136/bmjopen-2014-004904
|View full text |Cite
|
Sign up to set email alerts
|

Safety culture in a pharmacy setting using a pharmacy survey on patient safety culture: a cross-sectional study in China

Abstract: ObjectiveTo explore the attitudes and perceptions of patient safety culture for pharmacy workers in China by using a Pharmacy Survey on Patient Safety Culture (PSOPSC), and to assess the psychometric properties of the translated Chinese language version of the PSOPSC.DesignCross-sectional study.ParticipantsData were obtained from 20 hospital pharmacies in the southwest part of China.MethodsWe performed χ2 test to explore the differences on pharmacy staff in different hospital and qualification levels and count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
41
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 31 publications
8
41
9
1
Order By: Relevance
“…The average PRR for the patient safety culture (74.7%) in the Abu Dhabi Emirate is more than that in previous studies performed in Taiwan, China, Malaysia and the USA . The result suggested that the significance of the support of the values of patient safety in the community pharmacy practice is realised by the community pharmacists in Abu Dhabi.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…The average PRR for the patient safety culture (74.7%) in the Abu Dhabi Emirate is more than that in previous studies performed in Taiwan, China, Malaysia and the USA . The result suggested that the significance of the support of the values of patient safety in the community pharmacy practice is realised by the community pharmacists in Abu Dhabi.…”
Section: Discussionmentioning
confidence: 57%
“…Although the response rate among the pharmacists was 70.6%, which was less than that of the study implemented in the USA and China (75%, 84%), it is considered a good response. A high response rate on the survey about patient safety perceptions might be a measure of the pharmacist's attentiveness …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Regarding another factor of patient care, many patients (177/6.0%) regarded resident competency in relation to drug side effects as poor. A large number of people are injured or die in hospitals due to adverse drug events each year, 34 and the delivery of unsafe medical care has resulted in a trend toward increasing conflict between physicians and patients in China. 35 Thus, patient safety should have particular importance, 36,37 and clinical pharmacy services in particular can contribute to improving patient safety and reducing hospital costs associated with medication errors.…”
Section: Discussionmentioning
confidence: 99%